2022
DOI: 10.7554/elife.78074
|View full text |Cite
|
Sign up to set email alerts
|

Injury-induced pulmonary tuft cells are heterogenous, arise independent of key Type 2 cytokines, and are dispensable for dysplastic repair

Abstract: While the lung bears significant regenerative capacity, severe viral pneumonia can chronically impair lung function by triggering dysplastic remodeling. The connection between these enduring changes and chronic disease remains poorly understood. We recently described the emergence of tuft cells within Krt5+ dysplastic regions after influenza injury. Using bulk and single cell transcriptomics, we characterized and delineated multiple distinct tuft cell populations that arise following influenza clearance. Disti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…9 Tuft cells have also been shown to expand in the lung in response to the influenza virus and SARS-CoV-2. 10,11 Vaughan's lab showed that in the lung, tuft cells arise from Krt5 + a Sci Immunol. 2021 Jan 8;6 (55).…”
Section: Mechanisms Of Dysplastic Lung Repair Following Viral Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Tuft cells have also been shown to expand in the lung in response to the influenza virus and SARS-CoV-2. 10,11 Vaughan's lab showed that in the lung, tuft cells arise from Krt5 + a Sci Immunol. 2021 Jan 8;6 (55).…”
Section: Mechanisms Of Dysplastic Lung Repair Following Viral Infectionmentioning
confidence: 99%
“…Vaughan focused on the impact of tuft cells, which are implicated in intestinal damage and repair, where they play a role in type 2 mucosal immunity, characterized by IL‐13, IL‐25, and metaplasia 9 . Tuft cells have also been shown to expand in the lung in response to the influenza virus and SARS‐CoV‐2 10,11 . Vaughan's lab showed that in the lung, tuft cells arise from Krt5 + progenitors.…”
Section: Beyond Acute Disease: Consequences Of Respiratory Virus Infe...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow up study, Barr and co‐workers characterised these lung ectopic tuft cells on a transcriptional level and were able to delineate different tuft cell populations. The authors found the tuft‐1, tuft‐2 and the undifferentiated population described by Montoro and co‐workers (see ‘Brush cells in the lower airways’) as well as a fourth population that was described as a ‘stressed’ tuft cell population (Barr et al., 2022; Montoro et al., 2018). The ‘stressed’ tuft cell population showed high expression of mitochondrial genes, such as Aqp5 , Hspb1 , Selenbp1 and Cbr2 .…”
Section: Introductionmentioning
confidence: 96%
“…The tuft‐2 cell population, enriched in genes associated with leukotriene synthesis, was characterised by the expression of the marker genes Alox5ap and Mgst3 . Notably, the post‐influenza lung tuft cells, expressing chemosensory cell markers that can also be found in tracheal brush cells, showed lower levels of Chat and Plcb2 when compared to tracheal brush cells (Barr et al., 2022). While these lung tuft cells show the transcriptional profile of chemosensory cells and, thus, have been identified as members of the chemosensory cell family, their function and role in viral infections remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%